2012
DOI: 10.3399/bjgp12x625148
|View full text |Cite
|
Sign up to set email alerts
|

Quality of care provided to people with dementia: utilisation and quality of the annual dementia review in general practice

Abstract: BackgroundPrimary care services are often the main healthcare service for people with dementia; as such, good-quality care at this level is important. AimTo measure the quality of care provided to people with dementia in general practice using routinely collected data, and to explore associated patient and practice factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
25
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 28 publications
(25 reference statements)
8
25
0
1
Order By: Relevance
“…[30][31][32] It has been shown that the quality of annual reviews done in primary care for dementia is suboptimal and, despite a high prevalence of vascular diseases, over one-quarter of individuals diagnosed with dementia are prescribed antipsychotic medications that are known to increase the risk of cerebrovascular accidents and mortality. 33 In the current study, the quality of care for vascular conditions and risk factors received by…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…[30][31][32] It has been shown that the quality of annual reviews done in primary care for dementia is suboptimal and, despite a high prevalence of vascular diseases, over one-quarter of individuals diagnosed with dementia are prescribed antipsychotic medications that are known to increase the risk of cerebrovascular accidents and mortality. 33 In the current study, the quality of care for vascular conditions and risk factors received by…”
Section: Introductionmentioning
confidence: 94%
“…33 In brief, primary care electronic and paper records of 1006 people with dementia from dementia registers of a stratified random sample of 52 general practices from five primary care trusts (PCTs) in Greater Manchester were examined by trained researchers, using a proforma tool designed and piloted for the study purpose. From these, 12 people who had revoked diagnoses or were deceased were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Ten 98,110,117,118,129,136,139,145,155,161 of the 11 studies found some evidence that people with dementia were less likely to receive the same quality of care or access to services as those without dementia. For instance, studies found that people with dementia were less likely to receive monitoring for diabetes-related problems 97,136 and had reduced access to treatment such as intravenous thrombolysis for stroke, 129 surgery for cataracts, 110 treatment for age-related macular degeneration (AMD) 98,117 or services for diabetes. 139,145 More details are provided in Table 4.…”
Section: Comprehensiveness and Equitymentioning
confidence: 99%
“…A small minority of GPs and practice nurses in this study described regaining some clinical autonomy by seeking opportunities to modify indicators to meet the needs of individual patients. While greater individual discretion in implementation of indicators appears to be attractive to the profession in terms of increased clinical autonomy, such flexibility may not lead to improved patient outcomes 30 and is potentially dangerous within the context of pay for performance, since it directly contradicts evidence on the importance of validity and reliability in developing performance indicators. 31 Calibrating the appropriate level of clinical autonomy is critical if pay for performance schemes are to have maximal impact on patient care.…”
Section: Implications For Research and Practicementioning
confidence: 99%